Robin hood and little john - Earnshaw, Rosie (Rosemary Smith England, 2006)
*Robin Hood and Little John* is a classic tale of friendship and adventure, where Robin Hood, the outlaw hero, meets Little John while crossing a narrow bridge. After a playful and challenging fight, they become close friends and join forces to rob from the rich and give to the poor. Together, they lead a band of Merry Men in Sherwood Forest, outwitting the Sheriff of Nottingham and fighting for justice.